Evidence of doubly uniparental inheritance of the mitochondrial DNA in Polititapes rhomboides (Bivalvia, Veneridae): Evolutionary and population genetic analysis of F and M mitotypes. (7th February 2019) - Chacón, Ginna M.; Arias‐Pérez, Alberto; Freire, Ruth; Martínez, Luisa; Nóvoa, Susana; Naveira, Horacio; Insua, Ana
Abstract: Doubly uniparental inheritance (DUI) is a particular mitochondrial DNA inheritance mode reported in a number of bivalves. DUI species show two types of mtDNA, one transmitted from females to daughters and sons (F mitotype) and another one from males to sons (M mitotype). In Veneridae, the existence of DUI has been investigated in several species but it was found in only two of them. In this study, we obtained partial sequences of rrnL, cytb and cox1 genes of males and females of Polititapes rhomboides from NW Spain and we demonstrated the existence of heteroplasmy in males, as expected under DUI. F and M mitotypes showed a taxon‐specific phylogenetic pattern and similar evolutionary rates. We focused on cox1 for population genetic analysis, examining separately F and M mitotypes, but also F mitotypes from females (F♀ ) and males (F♂ ). In all cases, cox1 bears signs of strong purifying selection, with no apparent evidence of relaxed selection in the M genome, while the divergence between F and M genomes is in agreement with the neutral model of evolution. The cox1 polymorphism, higher at the M than at the F genome, also shows clear footprints of genetic hitchhiking with favourable mutations at other mtDNA loci, except for F ♂ . In terms of population structure, results suggest that the pattern depends on the examined mitotype (F, F♀, F♂ or M). Abstract : This work reports a DUI case in Veneridae, a family where this particular inheritance mode was not always found. Female (F) and male (M) mitotypes differ at 10–12% of their nucleotides, displaying a taxon‐specific phylogenetic pattern and similar evolutionary rates. M genomes do not seem to be under less stringent selective constraints than F genomes, and their polymorphisms show footprints of hitchhiking with linked favorable mutations. The pattern of population structure appears to depend both on mitotype and on sex.